2020
DOI: 10.1302/0301-620x.102b4.bjj-2019-0632.r3
|View full text |Cite
|
Sign up to set email alerts
|

The interobserver reliability of the diagnosis and classification of scaphoid fractures using high-resolution peripheral quantitative CT

Abstract: Aims Besides conventional radiographs, the use of MRI, CT, and bone scintigraphy is frequent in the diagnosis of a fracture of the scaphoid. However, which techniques give the best results remain unknown. The investigation of a new imaging technique initially requires an analysis of its precision. The primary aim of this study was to investigate the interobserver agreement of high-resolution peripheral quantitative CT (HR-pQCT) in the diagnosis of a scaphoid fracture. A secondary aim was to investigate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The CT also has a high specificity but a lower sensitivity; however, it is often preferred to the MRI as it is cheaper and more readily available (1,4,5). High-resolution peripheral quantitative computed tomography (HR-pQCT) represents an innovative option in detecting scaphoid fractures (6)(7)(8). Since the first results have only recently been published, its use is not yet widely established in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The CT also has a high specificity but a lower sensitivity; however, it is often preferred to the MRI as it is cheaper and more readily available (1,4,5). High-resolution peripheral quantitative computed tomography (HR-pQCT) represents an innovative option in detecting scaphoid fractures (6)(7)(8). Since the first results have only recently been published, its use is not yet widely established in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found that HR-pQCT is a feasible and reliable technique for scaphoid fracture diagnosis 29 , with "almost perfect" interobserver agreement (Fleiss kappa, 0.91) according to the guidelines by Landis and Koch 35 . In the present Fig.…”
Section: Discussionmentioning
confidence: 91%
“…All HR-pQCT scans were evaluated by a musculoskeletal radiologist. In a previous study, the interobserver agreement for 4 observers (2 musculoskeletal radiologists and 2 orthopaedic trauma surgeons) was shown to be almost perfect regarding scaphoid fracture diagnosis with HR-pQCT in patients with a clinically suspected scaphoid fracture 35 . The observers evaluated each HR-pQCT scan independently and were asked to determine the presence of a scaphoid fracture or other fracture (i.e., distal radial, carpal, metacarpal) on the basis of their expert opinion and to classify the scaphoid fracture, if present, according to the Herbert classification system (Fig.…”
Section: Scan Evaluationmentioning
confidence: 93%
“…Of trusts, 86.8% provided a second-line imaging 10–28 days after the initial injury; 63.9% used MRI and 27% used CT as second-line imaging (4). Conventional radiographs, MRI, CT, and bone scintigraphy are all frequently used in diagnosing SFs, but which technique provides the most accurate and cost-efficient results remains unclear (10). A systematic review, including 42 articles investigating 51 different diagnostic tools in 2507 patients, recently showed that MRI has the highest sensitivity and specificity for diagnosing SFs in comparison to CT, bone scintigraphy, and ultrasound (7).…”
Section: Discussionmentioning
confidence: 99%